ANALISIS PENERAPAN COST OF QUALITY UNTUK MENINGKATKAN KUALITAS PRODUK PADA PERUSAHAAN TAHU BULAT PD JEMPOL DI KABUPATEN CIAMIS - Gita Guntari; Dara Istia Aisyah; Asep Syarif Ismail (MANABIS: Jurnal Manajemen dan Bisnis, 2024)
Competition in the business sector requires that every company needs to produce quality products. This can be done by always checking and standardizing product quality. The costs incurred for these needs are often called quality costs or quality costs. The purpose of this research is to find out the extent of the quality of quality carried out by the round tofu company PD Jempol located in Ciamis Regency to improve the quality of its products. The method used by the author is a descriptive qualitative method. The data sources used are primary and secondary data sources obtained from interviews, observations and literature studies. The results of the research show that from the components taken, it can be concluded that the PD Jempol Round Tofu Company has implemented quality costs but needs to maximize the Cost of Quality in the business carried out.